Grids / The Structure of Graphic Design - Jute Andre; Rotovision (1996)
Introduction, The Purpose of the Grid, Elements of the Grid, Making a Quick Grid, Constructing a Proper Grid, Grid and Template and Stylebook, Introducing the Free Grids, Grids at Work, Index, Acknowledgements.
Introduction, The Purpose of the Grid, Elements of the Grid, Making a Quick Grid, Constructing a Proper Grid, Grid and Template and Stylebook, Introducing the Free Grids, Grids at Work, Index, Acknowledgements.